2013
DOI: 10.5455/vetworld.2013.131-133
|View full text |Cite
|
Sign up to set email alerts
|

Study on bacterial flora in the Hanuman langur Presbytis entellus of the Gujarat state, India

Abstract: Aim:To study the prevalence of bacterial flora in the Hanuman langur (Presbytis entellus) of the Gujarat state Material and Methods: Thirty hanuman langur (Presbytis entellus) (20 male and 10 female), were screened for bacterial flora during the period of June, 2010 to March, 2011. Hanuman langur (Presbytis entellus) were screened by culture of nasal, oral and rectal swabs during routine health monitoring and samples incubated using appropriate media and specific selective culture methods. Bacterial organisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge and based on available literature, isolation of Salmonella from swamp deer, lady Amherst pheasant and white peafowl appears to be for the first time in the world. In previous studies Salmonella was isolated from grey langur [20], hyena [21], leopard [22], golden pheasants [23] and ostrich [24]. The isolation rate of Salmonella from the feces of all captive wildlife was 3.1% and by direct PCR assay, detection rate was found to be 5.7%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge and based on available literature, isolation of Salmonella from swamp deer, lady Amherst pheasant and white peafowl appears to be for the first time in the world. In previous studies Salmonella was isolated from grey langur [20], hyena [21], leopard [22], golden pheasants [23] and ostrich [24]. The isolation rate of Salmonella from the feces of all captive wildlife was 3.1% and by direct PCR assay, detection rate was found to be 5.7%.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies Salmonella was isolated from grey langur [20], hyena [21], leopard [22], golden pheasants [23] and ostrich [24]. The isolation rate of Salmonella from the feces of all captive wildlife was 3.1% and by direct PCR assay, detection rate was found to be 5.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of TB in elephants in India, Thailand, Sri Lanka, Malaysia, Nepal and Laos have also confirmed transmission between humans and elephants (11, 30, 33, 54–56). Mtb has also been found in other wildlife in these countries, including free-living hanuman langurs in India and free-ranging and captive macaques in four Asian countries (10, 57).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis, caused by Mtb, has been reported in cattle in rural areas of Africa, including the Eastern Cape Province of South Africa, as well as in captive wildlife and pets (59). However, infections with Mtb have been discovered only recently in free-ranging wildlife in Asia (1012). Although animals are typically considered dead-end hosts for Mtb, there is evidence that infected elephants are capable of spreading infection to other elephants and different species, including humans (1316).…”
Section: Introductionmentioning
confidence: 99%
“…One study from a zoological collection in India reported TB in spotted deer [50], while a similar study in Pakistan reported TB in spotted deer and two antelopes, namely, chinkara gazella and black buck [62]. A few studies have reported TB from langur in India and rhesus monkey in Nepal [63,64], and these may be associated with M. tuberculosis transmission from contact with humans as in South Asia as there are many feral monkeys residing in communities. However, TB in wildlife in South Asia has not been adequately studied to fully understand the impact.…”
Section: Other Cases Of Tb In Wildlife In South Asiamentioning
confidence: 99%